Fathers of children with cancer : a narrative inquiry : a thesis presented in partial fultilment of the requirements for the degree of Doctor of Clinical Psychology at Massey University, Albany, New Zealand - Cluley, Sarah Marie (Massey University, 2015)
Receiving a diagnosis of childhood cancer can be a life-changing event for the child and their entire family. Parents of the sick child, in particular, are faced with the weight of responsibility for treatment decisions and caregiving, and often experience significant emotional, financial, social, and physical challenges during the treatment process. Mothers have traditionally been the focus of research in this area, and there is a paucity of in-depth, qualitative studies exploring the experiences of fathers, from their own perspectives. The current study explores the experiences of fathers of children with cancer in Auckland, New Zealand. Recruitment of participants was carried out with the help of the local Child Cancer Foundation (CCF). Twelve fathers of children diagnosed with cancer within the last five years responded and participated in narrative interviews, in which they were also invited to bring along objects of significance. Data was analysed through a narrative analytic lens and a subsequent focus on roles: the ways in which fathers constructed a sense of self through the different roles embedded in their narratives. This focus on roles led to an exploration of the ways in which different roles of fatherhood and manhood were central to the ways in which participants constructed their experiences of being a father of a child with cancer. An exploration of the overarching role of Cancer Dad provided a framework to look at how this role was manifested through four key ideas: taking control, finding strength, juggling responsibilities, and managing relationships. Within the idea of taking control, the roles of Decision Maker, Active Advocate, and Practical Policeman are explored. In relation to finding strength, the roles of Emotional Rock and Lone Wolf are examined, and in regards to juggling responsibilities, the roles of Breadwinner and Caregiver are discussed. Finally, within the idea of managing relationships, fathers’ constructions of the roles of Father, Husband, and Family Man are explored. This study is important in its use of roles as a means of understanding fathers’ experiences of their child’s cancer, and its inclusion of objects and recognition of their significance as narrative devices which can enrich the research process. However, perhaps the most important contribution is to the advancement of some understanding of how fathers understand their place throughout the challenges of their child’s cancer. Finally, this study also provides practical ideas for change, with the aim that support organisations and health professionals may provide more effective support services for fathers of children with cancer.
Keywords: Fathers; Psychology; Cancer; Patients; Family relationships; Cancer in children